2012
DOI: 10.1098/rsbl.2012.0197
|View full text |Cite
|
Sign up to set email alerts
|

Group size elicits specific physiological response in herbivores

Abstract: ).With increasing group size, individuals commonly spend less time standing head-up (scanning) and more time feeding. In small groups, a higher predation risk is likely to increase stress, which will be reflected by behavioural and endocrine responses. However, without any predator cues, we ask how the predation risk is actually processed by animals as group size decreases. We hypothesize that group size on its own acts as a stressor. We studied undisturbed groups of sheep under controlled pasture conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
1
8
1
1
Order By: Relevance
“…While, this data was disagreed with previous finding of Faerevik et al (2007) and Sabek et al, (2017) who find not significantly effect of group size on growth parameters. Table (3) showed that, there are a significant decrease in cortisol level with the group size increasing this data was in agreement with previous work of Michelena et al (2012) who reported that, cortisol concentration in sheep decreased as a group size increased. While, it disagreed with finding of Veissier et al (1998); Abdelfattah et al, (2013); Ahmed et al, 2017and Sabek et al (2017) who reported that, group size did not alter circulating cortisol.…”
Section: -Body Condition Scoresupporting
confidence: 91%
See 1 more Smart Citation
“…While, this data was disagreed with previous finding of Faerevik et al (2007) and Sabek et al, (2017) who find not significantly effect of group size on growth parameters. Table (3) showed that, there are a significant decrease in cortisol level with the group size increasing this data was in agreement with previous work of Michelena et al (2012) who reported that, cortisol concentration in sheep decreased as a group size increased. While, it disagreed with finding of Veissier et al (1998); Abdelfattah et al, (2013); Ahmed et al, 2017and Sabek et al (2017) who reported that, group size did not alter circulating cortisol.…”
Section: -Body Condition Scoresupporting
confidence: 91%
“…This result disagrees with Telezhenko et al (2012) as well as Hesham and Mohamed (2013) found that, group size had no effect on movement; Michelena et al (2012) who reported that, with increasing group size, individuals commonly spend less time standing and moving respectively.…”
Section: 2-posture 121-standing and Walking Frequency And Durationcontrasting
confidence: 56%
“…B 372: 20160239 of these studies found that individuals in larger groups have higher glucocorticoid concentrations relative to individuals in smaller groups (meadow voles [131]; African elephants [132]; cliff swallows [133]; American red squirrels [134]; rhesus monkeys [135]; king penguins [136]; see also review [137]). By contrast, other studies have found that individuals in smaller groups had higher glucocorticoid concentrations (sheep [138]; prairie voles [139]). Two other studies found that intermediate group size was optimal (yellow baboons [78]; ring-tailed lemurs [140]).…”
Section: (I) Glucocorticoidsmentioning
confidence: 58%
“…Studies on group size effects on glucocorticoid output yielded a heterogeneous pattern across taxa, including primates, rodents, ungulates, and birds. While the majority of studies found a positive correlation between GC secretion and group size (Foley et al 2001;Raouf et al 2006;Dantzer et al 2013;Dettmer et al 2014), there were also studies reporting opposite findings (Michelena et al 2012;Blondel et al 2016), or no link (Snaith et al 2008;Ebensperger et al 2011). In principle, both, larger and smaller groups inflict energetic costs on individuals based on resource competition and predation risks (Chapman and Chapman 2000), which in turn may cause elevated GC concentrations.…”
Section: Introductionmentioning
confidence: 99%